Stress intensity factor monitoring under cyclic loading by digital image correlation. Issue 10 (15th May 2018) - Mokhtarishirazabad, M.; Lopez‐Crespo, P.; Zanganeh, M.
Abstract: In the present work, a methodology for structural health monitoring based on a combination of digital image correlation and an analytical elastic solution is presented. To this end, full‐field displacement around a crack tip in a CT sample made of 2024‐T351 Al alloy under cyclic loading was monitored at different load levels. An analytical solution based on Williams' model was used to evaluate the experimental value of the stress intensity factor (SIF) in a continuous fashion during cyclic loads. It was observed that by increasing the loading amplitude in the cyclic loading, the difference between nominal and experimental estimation of SIF increased due to the crack tip plasticity effect, which was not considered in the nominal evaluations. To consider the plasticity effect, Irwin's approach was employed. The results showed that the proposed method can successfully monitor the evolution of SIF of a sample under cyclic loading until the sudden fracture of the sample.